2021
DOI: 10.3389/fonc.2021.742761
|View full text |Cite
|
Sign up to set email alerts
|

The Oncology Safety of Diagnostic Hysteroscopy in Early-Stage Endometrial Cancer: A Systematic Review and Meta-Analysis

Abstract: BackgroundHysteroscopy is becoming a common method for the diagnosis of uterine disorders in developed countries. However, hysteroscopy might worsen the prognosis of endometrial cancer because it could cause cancer dissemination into the peritoneal cavity through the fallopian tubes. Objective: The aim of this systematic review and meta-analysis was to explore the oncological safety of hysteroscopy for early-stage endometrial cancer.Search StrategyEligible studies were obtained from PubMed, Embase, and the Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Whether the malignant cells disseminated into the peritoneal cavity during diagnostic hysteroscopy can survive, colonize, invade the normal tissue, and worsen the prognosis of patients is unknown. A systematic review and meta-analysis by Du et al showed that for endometrial cancer, although can increase the risk of spreading of malignant cells, diagnostic hysteroscopy did not worsen the prognosis (13). With 127 type II endometrial cancer cases included, the study conducted by Ribeiro et al also reported that compared with traditional D&C, diagnostic hysteroscopy did not increase the risk of recurrence and all-cause death (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether the malignant cells disseminated into the peritoneal cavity during diagnostic hysteroscopy can survive, colonize, invade the normal tissue, and worsen the prognosis of patients is unknown. A systematic review and meta-analysis by Du et al showed that for endometrial cancer, although can increase the risk of spreading of malignant cells, diagnostic hysteroscopy did not worsen the prognosis (13). With 127 type II endometrial cancer cases included, the study conducted by Ribeiro et al also reported that compared with traditional D&C, diagnostic hysteroscopy did not increase the risk of recurrence and all-cause death (35).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis by Du et al. showed that for endometrial cancer, although can increase the risk of spreading of malignant cells, diagnostic hysteroscopy did not worsen the prognosis ( 13 ). With 127 type II endometrial cancer cases included, the study conducted by Ribeiro et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the largest retrospectives multicentric studies published to date, that was based in a series of 1731 women of whom 1044 were diagnosed with hysteroscopy and 687 with Pipelle biopsy, revealed that there was no association of hysteroscopy with the risk of relapse (hazards ratio (HR) 1.24, 95% confidence interval [CI] 0.92 to 1.66; P ¼ 0.16) or overall survival (HR 0.95, 95% CI 0.70 to 1.29; P ¼ 0.76) [51]. Several other smaller cohorts have been published that were summarized recently in a systematic review that included 3,980 patients of whom whom1357 patients had undergone hysteroscopy and2623 had not [52]. The study revealed that there was no association of hysteroscopy with disease free survival and overall survival, therefore, denoting that it should be considered a safe diagnostic and treatment method for patients with early-stage endometrial carcinoma.…”
Section: Surgical Investigation and Treatmentmentioning
confidence: 99%
“…It enables visualisation of the uterine cavity and is more accurate than pelvic ultrasound in assessing the endometrial cavity [1][2][3][4] . It has a high diagnostic accuracy for endometrial cancer and is not associated with worse prognosis in early-stage endometrial cancer 5 . Performing hysteroscopic procedures in an outpatient setting reduces the need for operative theatres and hence healthcare costs [6][7][8] .…”
Section: Introductionmentioning
confidence: 98%